Short-Term Application of Polymer-Coated Mono-Ammonium Phosphate in a Calcareous Soil Affects the Pools of Available Phosphorus and the Growth of Hypericum × moserianum (L.) - Pizzeghello, Diego; Schiavon, Michela; Maretto, Laura; Stevanato, Piergiorgio; Ertani, Andrea; Altissimo, Adriano; Nardi, Serenella (Frontiers in Sustainable Food Systems, 2019)
Mineral phosphorus (P) fertilization in calcareous soils is not efficient enough to ensure optimal plant growth. Therefore a higher P input is generally needed. Polymer-coated fertilizers are a promising fertilizer category that seems to affect soil extractable P, thus permitting a reduction in fertilizer rates. We tested this hypothesis in a short-term (45 days) field trial by evaluating both the agronomic and the environmental implications. In this study, two conventional fertilizers (single superphosphate, SSP; mono-ammonium phosphate, MAP) and a slow P-release fertilizer (polymer-coated MAP, PCMAP) were tested for their effects on soil P pools by combining different P rates and degrees of coating. The P soil test was determined with either Olsen or Mehlich-3 solution (available P), whereas the P soil release was estimated through water extraction. The efficiency of fertilizers was evaluated by assessing the growth of Hypericum × moserianum (L.) plants. As expected, both SSP and MAP influenced the soil Mehlich-3-P, Olsen-P, and water-P, as concentrations increased with the fertilizer rate. Conversely, PCMAP decreased the soil extractable P with increasing coating. The plant dry weight and P content linearly correlated with the fertilizer rate for SSP and MAP, whilst displayed a quadratic correlation for PCMAP. This result indicates the underdosing for conventional fertilizers, and the achievement of maximum plant yield for PCMAP. With reference to the soil test P with water-P, the presence of change points showed low water-P release concentrations for PCMAP and SSP, and high water-P release for MAP. In conclusion, in the short-term period both soil extractable P and water-P depend on the type of fertilizer, whereas the amount of added P has rather a secondary role. PCMAP, in particular, ensures high plant P use efficiency with minimum environmental impacts.